The Prevalence of Psychiatric Distress and Associated Risk Factors among College Students Using GHQ-28 Questionnaire - Jalal POOROLAJAL; Ali GHALEIHA; Nahid DARVISHI; Shahla DARYAEI; Soheila PANAHI (Tehran University of Medical Sciences, 2017)
Background: Adolescent and young adults are at increased risk of psychiatric distress and serious disability. We estimated the prevalence and associated risk factors of psychiatric distress among the college students of Hamadan University of Medical Sciences, Iran. Methods: We performed this cross-sectional study, from Jan to May 2016 at Hamadan University of Medical Sciences, Hamadan, Iran. Students filled out voluntarily an anonymous self-administered questionnaire, including demographic characteristics, personal information, behavioral risk factors, and a validated Persian version of the GHQ-28 questionnaire, including somatic symptoms (items 1-7), anxiety/insomnia (items 8-14), social dysfunctions (items 15-21), and severe depression (items 22-28). Results: Of 1259 participants, 518 (41.1%) had psychiatric distress, 166 (13.2%) had heterosexual intercourse, 100 (8.0%) had homosexual intercourse, 204 (16.2%) were smokers (31.6% in males and 6.3% in females), 124 (9.9%) reported a history of using opium/psychedelic substances, 204 (16.2%) reported suicide thought, and 103 (8.2%) had attempted suicide at least once in the past. After adjusting odds ratio (95% CI) for age and sex, psychiatric distress were significantly associated with emotional breakdown 2.67 (2.09, 3.40), heterosexual intercourse 2.56 (1.82, 3.62), homosexual intercourse 2.42 (1.57, 3.71), smoking 3.19 (2.29, 4.45), substance abuse 5.03 (3.26, 7.76), suicide thought 7.81 (5.42, 11.27), suicide attempt 5.64 (3.49, 9.12), uninterested in the discipline 2.29 (1.70, 3.07), and non-optimistic about future 2.16 (1.63, 2.86). Conclusion: A majority of college students had psychiatric distress and a substantial number of them reported one or more high-risk behaviors that if neglected, may severely impair the students' function and influence their subsequent development and productive lives.